A patient with Korsakoff syndrome of psychiatric and alcoholic etiology presenting as DSM-5 mild neurocognitive disorder - Nikolakaros G; Kurki T; Myllymäki A; Ilonen T (Neuropsychiatric Disease and Treatment, 2019)
Georgios Nikolakaros,1,2 Timo Kurki,3,4 Arttu Myllymäki,1 Tuula Ilonen51Satakunta Hospital District, Psychiatric Care Division, General Psychiatry Outpatient Clinic, Pori, Finland; 2HUS Medical Imaging Center, Department of Clinical Neurophysiology, Helsinki University Hospital, Helsinki, Finland; 3Terveystalo Pulssi Medical Center, Turku, Finland; 4Department of Radiology, University of Turku, Turku, Finland; 5Department of Psychiatry, University of Turku, Turku, FinlandBackground: Wernicke’s encephalopathy (WE) and Korsakoff syndrome (KS) are underdiagnosed. The DSM-5 has raised the diagnostic threshold by including KS in the major neurocognitive disorders, which requires that the patient needs help in everyday activities.Methods: We report clinical, neuropsychological, and radiological findings from a patient who developed Wernicke-Korsakoff syndrome as a result of alcohol use and weight loss due to major depression. We assess the diagnosis in the context of the scientific literature on KS and according to the DSM-IV and the DSM-5.Results: The patient developed ataxia during a period of weight loss, thus fulfilling current diagnostic criteria of WE. WE was not diagnosed, but the patient partially improved after parenteral thiamine treatment. However, memory problems became evident, and KS was considered. In neuropsychological examination, the Logical Memory test and the Word List test were abnormal, but the Verbal Pair Associates test was normal (Wechsler Memory Scale-III). There were intrusions in the memory testing. The Wisconsin Card Sorting Test was broadly impaired, but the other test of executive functions (difference between Trail Making B and Trail Making A tests) was normal. There was atrophy of the mammillary bodies, the thalamus, the cerebellum, and in the basal ganglia but not in the frontal lobes. Diffusion tensor imaging showed damage in several tracts, including the uncinate fasciculi, the cinguli, the fornix, and the corona radiata. The patient remained independent in everyday activities. The patient can be diagnosed with KS according to the DSM-IV. According to the DSM-5, the patient has major neurocognitive disorders.Conclusions: Extensive memory testing is essential in the assessment of KS. Patients with a history of WE and typical clinical, neuropsychological, and radiological KS findings may be independent in everyday activities. Strict use of the DSM-5 may worsen the problem of Wernicke-Korsakoff syndrome underdiagnosis by excluding clear KS cases that do not have very severe functional impairment.Keywords: alcoholism, depressive disorder, diffusion tensor imaging, Korsakoff syndrome, neurocognitive disorders, Wernicke encephalopathy